1993
DOI: 10.1016/0958-1669(93)90053-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-viral approaches to gene therapy

Abstract: Several advances in non-viral gene transfer technology have been reported over the past year. Cationic lipids have been successfully used to deliver genes in vivo, providing a clear alternative to recombinant viruses. In addition, investigators have demonstrated that direct application of DNA via injection or particle bombardment can be used for vaccination. Analysis of the mechanisms employed by viruses to invade cells has demonstrated a crucial role for membrane-active proteins or peptides in the entry proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…Specifically, it has been shown that cationic liposomes are clinically well tolerated, easy to produce, noninfectious, nonimmunogenic, and able to transfect slowly dividing cells. 3,4 Receptor-mediated gene delivery can potentially improve efficiency and safety further by selectively targeting a cell population expressing the surface receptor for a ligand. The efficiency of gene transfer by receptor-mediated endocytosis of polycation -DNA complexes has been enhanced by the incorporation of endosomolytic agents, such as adenoviral capsids or fusogenic peptides.…”
mentioning
confidence: 99%
“…Specifically, it has been shown that cationic liposomes are clinically well tolerated, easy to produce, noninfectious, nonimmunogenic, and able to transfect slowly dividing cells. 3,4 Receptor-mediated gene delivery can potentially improve efficiency and safety further by selectively targeting a cell population expressing the surface receptor for a ligand. The efficiency of gene transfer by receptor-mediated endocytosis of polycation -DNA complexes has been enhanced by the incorporation of endosomolytic agents, such as adenoviral capsids or fusogenic peptides.…”
mentioning
confidence: 99%
“…12 Cavifor the uptake of plasmid DNA into mammalian cells tation is well known as a powerful mechanism of tissue have been developed in the past, including coprecipidamage induction based on severe ultrastructural altertation with calcium phosphate, 1 use of polycations or lipations at the cellular and subcellular level. 13 Whereas a ids to form complexes with DNA, 2 encapsidation of plasdefined portion of shock wave-exposed cells is commid DNA into liposomes or erythrocyte ghosts, [3][4][5] pletely destroyed and reduced to cell debris (dependent exposure of cells to rapid pulses of high-voltage current, upon the applied number of discharges and their pulse ie electroporation, 6,7 receptor-mediated endocytosis of energy), the majority of cells surviving the shock wave-DNA-ligand complexes 8 and introduction of DNA into exposure procedure has been shown to continue to procells by direct microinjection 9 or on high-velocity tungliferate at a near normal rate. 14 Interestingly, different cell sten microprojectiles.…”
mentioning
confidence: 99%
“…20 Thus, the disadvantageous usage of the endosopropagation wave was focused to the second focus of the ellipsoid where a 2.5 ml silicone-stopper sealed polymal pathway, which is employed in receptor-mediated gene transfer, is omitted. 8 (4) The ineffectiveness of plaspropylene vial (Nunc, Wiesbaden, Germany) containing the respective suspended cells was positioned without mid DNA transfer across the nuclear membrane -limiting expression efficiency of successfully transferred, cytoany residual air in the vial. The position of the second focus was indicated by the intersection of two positioning plasmically localized nucleic acids -can be overcome potentially by utilization of nucleus-independent laser beams ( Figure 1).…”
mentioning
confidence: 99%
“…4 -7,26 A variety of liposomes and polymers have been developed and shown in recent years to be highly effective in gene transfer; however, most of these agents are nonspecific. 3,27,28 Targeting of nonviral gene delivery has been achieved by incorporating into the vectors ligands that can specifically recognize surface markers of the cells. Notably, transferrin incorporated into liposomes can substantially enhance efficiency of gene transfer mediated by the liposome.…”
Section: Discussionmentioning
confidence: 99%